Types of letter reversal among dyslexic students - Subramaniam, Vijayaletchumy; Abdan Nasir, Nadia Shuhada (Science Research Society, 2021)
This study is done to examine the issue of letter reversal among dyslexic students. The study objective is to identify the type of letter reversal among dyslexic students. The theory adopted in this study is the Levinson Theory (1994). The study sample comprises 10 dyslexic students from Dyslexia Center Malaysia in Ampang, Kuala Lumpur who experience severe letter reversal issues. This work adopts observation, interview and questionnaire methods. Meanwhile, the study tools used are the questionnaire forms and field notes. Eight letters with similar forms common to be in reversal among the dyslexia students based on Levinson Theory (1994), are letters ‘b’, ‘d’, ‘p’, ‘q’, ‘m’, ‘w’, ‘n’ and ‘u’ and they are chosen and enlisted in the questionnaire form. The questionnaire is then given to the respondents, or teachers at the dyslexia center to be answered. The study data are analyzed both qualitatively and quantitatively. The study finding shows that all the subjects have a reversal issue towards the letters. Nonetheless, the types of letters being reversed are different according to individuals.